2018
DOI: 10.1017/s0022215118001962
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hearing loss severity in tympanic membrane perforations in a sub-Saharan African setting

Abstract: BackgroundFactors specific to sub-Saharan Africa could have an impact on tympanic membrane perforation characteristics. Obtaining precise information on these characteristics and determinants of hearing loss severity would enable better management.ObjectiveTo determine the relationship between characteristics of tympanic membrane perforation and subsequent hearing impairment.MethodsA cross-sectional study of consenting patients presenting with tympanic membrane perforation was conducted. They were examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…1 On the other hand, there is a definite agreement regarding the size of the perforation: hearing loss will increase with the increasing size of a tympanic membrane perforation. [1][2][3] The volume of the middle ear and mastoid cell complex, involvement of manubrium mallei, and duration of perforations are other factors that may affect hearing. 1,4,5 The main goal of this study was to evaluate the effect of size, location and shape of the perforations on hearing by analysing pre-operative pure tone average (PTA) and air-bone gap (ABG) values of a large study group treated in a tertiary referral centre, which included over 400 cases.…”
Section: Introductionmentioning
confidence: 99%
“…1 On the other hand, there is a definite agreement regarding the size of the perforation: hearing loss will increase with the increasing size of a tympanic membrane perforation. [1][2][3] The volume of the middle ear and mastoid cell complex, involvement of manubrium mallei, and duration of perforations are other factors that may affect hearing. 1,4,5 The main goal of this study was to evaluate the effect of size, location and shape of the perforations on hearing by analysing pre-operative pure tone average (PTA) and air-bone gap (ABG) values of a large study group treated in a tertiary referral centre, which included over 400 cases.…”
Section: Introductionmentioning
confidence: 99%
“…21 In a multivariate logistic regression analysis on 67 patients (86 perforations) aged 10 and over size of perforation proved to be the only significant predictor of HL severity. 23 The logistical challenges of data collection in our study population due to age, remoteness, and resources mean that the variables measured in the literature cited above could unfortunately not be measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies also demonstrate increased HL with posterior perforations. Studies consistently utilize the manubrium mallei as the angled division between anterior and posterior 6–8,10,12,15,23 . However, the exact classification of location varies somewhat and is not often illustrated, making comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation causes a decrease in ossicular coupling due to the inability to transmit pressure across the TM. A study set in the sub-Saharan African region showed a link between hearing loss and TM perforation, including the site of perforation [8]. There is also said to be a strong correlation between age and hearing function in such individuals, especially with conductive hearing loss, which was less severe in children than in patients over the age of 30 [9].…”
Section: Introductionmentioning
confidence: 99%